UPAYA MENINGKATKAN POTENSI PSIKOMOTORIK ANAK USIA DINI MELALUI PRAKTIK SALAT - Rikhanah, Rikhanah (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study discusses the enhancement of psychomotor potential in early childhood through the practice of prayer at Nusantara Kindergarten in Kualuh Hulu District, Labuhanbatu Utara Regency. The problem of this research is formulated as how the psychomotor potential is assessed before implementing the practice of prayer. What is the process of executing the practice of prayer and how the psychomotor potential is after applying the practice of prayer. The results obtained in this study show that of the 15 samples of children studied, the average psychomotor potential observed in the pre-cycle was 13.33% (2 children), in cycle I it was 66.66% (10 children) who had developed psychomotor potential. Then in cycle II, there was an increase to 93.33% (14 children) who experienced an increase in psychomotor potential. This indicates that the practice of prayer is effective in enhancing the psychomotor potential of early childhood.